Shattered : a memoir - Kureishi, Hanif (Ecco, an imprint of HarperCollinsPublishers, 2024)
A writer recounts his yearlong recovery in Rome following a fall that left him unable to walk, dictating reflections on his medical journey, parenthood, immigration, and writing, ultimately transforming his pain into a narrative that celebrates resilience, gratitude, and love amidst adversity.